The exporter wage premium when firms and workers are heterogeneous - Hartmut Egger; Peter Egger; Udo Kreickemeier; Christoph Moser (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
We set up a trade model with heterogeneous firms and a worker population that is heterogeneous in two dimensions: workers are either skilled or unskilled, and within each skill category there is a continuum of abilities. Workers with high abilities, both skilled and unskilled, are matched to firms with high productivities, and this leads to wage differentials within each skill category across firms. Self-selection of the most productive firms into exporting generates an exporter wage premium, and our framework with skilled and unskilled workers allows us to decompose this premium into its skill-specific components. We employ linked employer-employee data from Germany to structurally estimate the parameters of the model. Using these parameter estimates, we compute an average exporter wage premium of 5 percent. The decomposition by skill turns out to be quantitatively highly relevant, with exporting firms paying no wage premium at all to their unskilled workers, while the premium for skilled workers is 12 percent.
urn:nbn:de:bsz:14-qucosa-227402
Keywords: C31; F12; F15; J31; 330; Exporter wage premium; Heterogeneous firms; Ability differences of workers; Positive assortative matching; Trade and wage inequality